Role of ER Stress in Ventricular Contractile Dysfunction in Type 2 Diabetes - Takada, Akifumi; Miki, Takayuki; Kuno, Atsushi; Kouzu, Hidemichi; Sunaga, Daisuke; Itoh, Takahito; Tanno, Masaya; Yano, Toshiyuki; Sato, Tatsuya; Ishikawa, Satoko; Miura, Tetsuji (PLOS ONE, 2012)
Background Diabetes mellitus (DM) is associated with an increased risk of ischemic heart disease and of adverse outcomes following myocardial infarction (MI). Here we assessed the role of endoplasmic reticulum (ER) stress in ventricular dysfunction and outcomes after MI in type 2 DM (T2DM). Methodology and Principal Findings In hearts of OLETF, a rat model of T2DM, at 25∼30 weeks of age, GRP78 and GRP94, markers of ER stress, were increased and sarcoplasmic reticulum calcium ATPase (SERCA)2a protein was reduced by 35% compared with those in LETO, a non-diabetic control. SERCA2a mRNA levels were similar, but SERCA2a protein was more ubiquitinated in OLETF than in LETO. Left ventricular (LV) end-diastolic elastance (Eed) was higher in OLETF than in LETO (53.9±5.2 vs. 20.2±5.6 mmHg/µl), whereas LV end-systolic elastance and positive inotropic responses to β-adrenergic stimulation were similar in OLETF and LETO. 4-Phenylbutyric acid (4-PBA), an ER stress modulator, suppressed both GRP up-regulation and SERCA2a ubiquitination and normalized SERCA2a protein level and Eed in OLETF. Sodium tauroursodeoxycholic acid, a structurally different ER stress modulator, also restored SERCA2a protein level in OLETF. Though LV dysfunction was modest, mortality within 48 h after coronary occlusion was markedly higher in OLETF than in LETO (61.3% vs. 7.7%). Telemetric recording showed that rapid progression of heart failure was responsible for the high mortality rate in OLETF. ER stress modulators failed to reduce the mortality rate after MI in OLETF. Conclusions ER stress reduces SERCA2a protein via its augmented ubiquitination and degradation, leading to LV diastolic dysfunction in T2DM. Even at a stage without systolic LV dysfunction, susceptibility to lethal heart failure after infarction is markedly increased, which cannot be explained by ER stress or change in myocardial response to sympathetic nerve activation.